2010
DOI: 10.1007/s11243-010-9327-4
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, structural characterization and alcohol oxidation activity of a new mononuclear manganese(II) complex

Abstract: A manganese(II) complex of 2,4,6-tris(2-pyridyl)-1,3,5-triazine (tptz) has been synthesized and characterized by single-crystal X-ray diffraction, elemental analyses, IR, and UV-Vis spectroscopic techniques. Oxidation of alcohols to their corresponding aldehydes and ketones was conducted by this catalyst using oxone (2KHSO 5 ÁKH-SO 4 ÁK 2 SO 4 ) as an oxidant under biphasic reaction conditions (CH 2 Cl 2 /H 2 O) and tetra-n-butylammonium bromide as phase transfer agent under air at room temperature. Easy prepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…We reported on Mn(II), MnO 4 À and insoluble Mn products which show weak absorption bands characteristic of an {Mn 2 O 2 } core in the region of 600e700 cm À1 [13]. Using ESI(þ)eMS/MS at pH~4.5 we also showed that the mononuclear complex [Mn(tptz)(CH 3 COO)(OH 2 ) 2 ]NO 3 is not fully preserved and is in equilibrium with some cationic species [15]. In this case, a dissociative Mn-ligand process occurs in the water/ acetonitrile solution [15].…”
Section: Mn Oxides As True Catalysts For Water Oxidationmentioning
confidence: 84%
See 1 more Smart Citation
“…We reported on Mn(II), MnO 4 À and insoluble Mn products which show weak absorption bands characteristic of an {Mn 2 O 2 } core in the region of 600e700 cm À1 [13]. Using ESI(þ)eMS/MS at pH~4.5 we also showed that the mononuclear complex [Mn(tptz)(CH 3 COO)(OH 2 ) 2 ]NO 3 is not fully preserved and is in equilibrium with some cationic species [15]. In this case, a dissociative Mn-ligand process occurs in the water/ acetonitrile solution [15].…”
Section: Mn Oxides As True Catalysts For Water Oxidationmentioning
confidence: 84%
“…Using ESI(þ)eMS/MS at pH~4.5 we also showed that the mononuclear complex [Mn(tptz)(CH 3 COO)(OH 2 ) 2 ]NO 3 is not fully preserved and is in equilibrium with some cationic species [15]. In this case, a dissociative Mn-ligand process occurs in the water/ acetonitrile solution [15]. The experiment also showed that the most important reaction in the presence of Oxone ® is a "decoordination".…”
Section: Mn Oxides As True Catalysts For Water Oxidationmentioning
confidence: 88%
“…Catalyst 1 demonstrated a superior catalytic activity than those all of the Mn II complexes listed in Table except for the mononuclear Mn II complex reported by Boghaei and co‐workers (Table , Entry 2). Although this mononuclear complex exhibits 100 % conversion and selectivity, the oxidant used in this case was oxone, an unfavored oxidant for organic oxidation reactions. Furthermore, it should be noted that the non‐heme Mn II complex reported by Nam and co‐workers (Table , Entry 3) and a polymeric Mn II complex reported by Bagherzadeh and co‐workers (Table , Entry 6) showed 100 % selectivity with reasonable conversion but only when harmful oxidants were employed as part of catalytic system.…”
Section: Resultsmentioning
confidence: 99%
“…A number of methods are known for alcohol oxidations, but oxidations catalyzed by different coordination complexes such as Fe [19], Cu [20], Co [21], Mo [22], Pd [23], Mn [24], V [25] complexes in presence of H 2 O 2 as the oxidant are preferred now for their economic benefits and environmental acceptability.…”
Section: Catalytic Oxidation Of Benzyl Alcoholmentioning
confidence: 99%